Beckman Model 165 Multichannel Rapid Scanning UV-Vis Detector - Beckman Instruments, Inc.
This piece is the cover for Bulletin 7388A for the Model 165 UV-Vis detector used for liquid chromatography.
Keywords: Liquid chromatography; Ultraviolet spectroscopy; Scientific apparatus and instruments; Spectrophotometer; Beckman Instruments, Inc.